CHEMICAL HETEROGENEITY IN CARBONADO, AN ENIGMATIC POLYCRYSTALLINE DIAMOND - De S.; Heaney P.J.; Vicenzi E.P.; Wang J. (My University, 2001)
Carbonado, a polycrystalline variety of diamond, is characterized by unusual carbon isotope compositions with bulk δ13C values clustered tightly between −23 and −30‰ (relative to PDB). These values are significantly lighter than harzburgitic diamond (with a range in δ13C from −1 to −10‰) and fall near the lower extreme for eclogitic diamond (ranging from +3 to −34‰). In combination with textural and inclusion data, these isotopic compositions have led scientists to question whether carbonado originated in the mantle or in the crust. Previous studies of carbonado have revealed a bimodal grain size distribution that correlates with cathodoluminescence (CL) emissions. We believe that these textures result from a two-step growth process, and we have obtained additional chemical evidence that supports the identification of two distinct crystal populations. Ion microprobe analyses of a Central African carbonado reveal a bimodal distribution of δ13C values of −24 and −26‰ (with an instrumental precision of ±0.29‰). Secondary ion mass spectrometry analyses also demonstrate that this δ13C distribution coincides with variations in nitrogen abundance, and both of these chemical zonations correlate with CL emission signatures. A one-dimensional analysis of self-diffusion of carbon in diamond suggests that isotopic homogenization occurs extremely slowly, even under upper mantle conditions. Whereas the microscale distribution of carbon isotopes in carbonado does not constrain the temperature, pressure or time of carbonado formation, it does provide a geochemical signature that recorded the dynamics of the growth process.